Examining Self-Efficacy as a Mediating Factor in Urban Generation Z's Agripreneurial Interest - Dessy Iriani Putri; Lorenta In Haryanto; Rizki Adi Puspita Sari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This research investigates how the university environment, income expectations, family environment, and role models influence agripreneurial interest among urban Generation Z, with self-efficacy examined as a mediating variable. A quantitative research design was adopted, and data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, based on data from 88 Generation Z respondents in the JABODETABEK region. The findings reveal that self-efficacy, income expectations, and the university environment exert a significant direct influence on agripreneurial interest, while family environment and role models do not. Furthermore, the university environment significantly influences agripreneurial interest indirectly through self-efficacy, whereas other variables do not show significant indirect effects. This study is among the limited empirical research investigating self-efficacy as a mediating mechanism shaping agripreneurial interest among urban Generation Z. It contributes theoretically by positioning self-efficacy as a key psychological mechanism that explains how the university environment shapes agripreneurial interest. This study contributes theoretically by identifying self-efficacy as a key mediating mechanism that explains how the university environment shapes agripreneurial interest among urban Generation Z. The novelty of this research lies in empirically positioning self-efficacy as a central explanatory variable in agripreneurship studies on farmer regeneration, an area underexplored in the existing literature.